ANALYZING MEDIA CONVERGENCE IN THE HIJABER COMMUNITY FOR DISSEMINATING RELIGIOUS VALUES IN INDONESIA - Meidina, Aulia Putri (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
Media convergence has resulted in many transformations in religious social dynamics, including the adoption of a 'marketing' approach by the Hijaber Community in Indonesia to promote religious principles. This community utilises a range of social media channels to disseminate these religious beliefs, aiming to enhance their visibility and acceptance among both online and offline populations. The objective of this study is to provide a description of the various types of media convergence seen within the community and analyse their influence on the community's development in the online realm. The study employed a qualitative netnography methodology to examine the social media accounts utilised by the subjects. The data was subsequently examined with the convergence culture hypothesis pioneered by Henry Jenkins. The findings indicated that the media convergence process gave rise to two distinct types of convergence culture: participation culture and collective intelligence. This type of participatory culture is seen in the uploading of twibbons and the posts made by community followers, as well as the growing number of members in the Hijaber Community. Furthermore, communal intelligence is evident through the use of reels and IG live, which are available for access at any given moment.Konvergensi media telah memunculkan sejumlah perubahan dalam kehidupan sosial keagamaan, salah satunya adalah strategi ‘pemasaran’ nilai-nilai keagamaan yang dilakukan oleh komunitas Hijaber Community di Indonesia. Komunitas ini mengintegrasikan berbagai platform media sosial untuk mempromosikan nilai-nilai keagamaan tersebut sehingga menjadi lebih banyak dikenal oleh masyarakat online dan offline. Penelitian ini bermaksud untuk mendeskripsikan apa saja bentuk-bentuk konvergensi media dalam komunitas tersebut dan bagaimana konvergensi itu memberikan dampak perkembangan komunitas mereka di dunia maya. Penelitian dilakukan dengan menggunakan pendekatan kualitatif netnografi dengan menelusuri berbagai akun sosial media yang mereka gunakan. Data kemudian dianalisis dengan menggunakan teori budaya konvergensi yang digagas oleh Henry Jenkins. Hasil penelitian menunjukkan bentuk-bentuk budaya konvergensi yang muncul dari proses konvergensi media yaitu budaya partisipasi dan kecerdasan kolektif. Bentuk budaya partisipasi ini terlihat dalam unggahan twibbon dan postingan follower komunitas serta bertambahnya anggota komunitas Hijaber Community. Sedangkan kecerdasan kolektif dalam terlihat dari reels dan IG live yang dapat diakses setiap saat.